2020
DOI: 10.1111/evo.13941
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogeography of West African amphibians and reptiles

Abstract: Comparative phylogeographic studies often support shared divergence times for co‐distributed species with similar life histories and habitat specializations. During the late Holocene, West Africa experienced aridification and the turnover of rain forest habitats into savannas. These fragmented rain forests harbor impressive numbers of endemic and threatened species. In this setting, populations of co‐distributed rain forest species are expected to have diverged simultaneously, whereas divergence events for spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…This bears similarities to phylogenetic patterns among genera of African dwarf toads with the divergence of Altiphrynoides , which is endemic to the Ethiopian Highlands, from a clade containing Central and West African genera occurring in the earliest Miocene (Liedtke et al, 2016), as well as divergences between rainforest trees from eastern and West and Central Africa (Couvreur et al, 2008). More recent divergences within species that may represent undescribed lineages, including C. alleni and C. crassipes , appear to have occurred during the Pliocene and Pleistocene, which is similar to other recent studies of forest‐restricted tropical anurans in this region (Bell et al, 2017; Leaché et al, 2019, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This bears similarities to phylogenetic patterns among genera of African dwarf toads with the divergence of Altiphrynoides , which is endemic to the Ethiopian Highlands, from a clade containing Central and West African genera occurring in the earliest Miocene (Liedtke et al, 2016), as well as divergences between rainforest trees from eastern and West and Central Africa (Couvreur et al, 2008). More recent divergences within species that may represent undescribed lineages, including C. alleni and C. crassipes , appear to have occurred during the Pliocene and Pleistocene, which is similar to other recent studies of forest‐restricted tropical anurans in this region (Bell et al, 2017; Leaché et al, 2019, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…The Bayesian species delimitation analyses supported either 9, 11 or 12 ‘species’ based on the combination of priors. As also recovered by Leaché et al (2020), the population of C. derooi from the Atewa Range of south‐central Ghana (Kouamé et al, 2007; Hillers et al, 2009; Lindsell et al, 2019) likely corresponds to an undescribed species; note that the location indicated in Leaché et al (2020) is incorrect as it is in south‐western Ghana which is well outside the recognized range for this species (Channing & Rödel, 2019; Hillers et al, 2009). Substructure within C. alleni was well supported in all analyses, although further splitting of subclades 1 (in the Fouta Djallon highlands) and 2 (Figure 1b, ) varies based on the configuration of priors used.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our study highlights the difficulties of unravelling diversification histories in a region subjected to complex historical processes (Lohman et al, 2011; Frantz et al., 2013; Leaché, Oaks, Ofori‐Boateng, & Fujita, 2020). One limitation of current models is that they are restricted to testing fairly simple demographic histories (Oaks, Siler, & Brown, 2019; Terhorst & Song, 2015), which approximate diversification processes of taxa subjected to complex events such as glacial cycles or repeated volcanic events (Lohman et al, 2011).…”
Section: Discussionmentioning
confidence: 72%
“…Speciation processes have often been inferred from relationships between genealogical and geographical patterns (e.g., Camargo et al 2010), with 'phylogeography' now a burgeoning discipline uniting intraspecific (i.e., population-level) and macroevolutionary perspectives (Avise 2009). Comparative analysis of intra-and inter-specific patterns has revealed spatial features driving diversification and lineage reticulation at continental scales (Burbrink et al 2018, Wollenberg Valero et al 2019, Leaché et al 2020). Yet relating spatial and temporal patterns is not always straightforward, with juxtaposition of contemporary geographics with aspects of modern biodiversity sometimes yielding contradictory patterns.…”
Section: Biogeographic Templates and Taxonomic Reverberations In Aspimentioning
confidence: 99%